Positive Solutions for Nonlinear Singular Differential Systems Involving Parameter on the Half-Line - Lishan Liu; Ying Wang; Xinan Hao; Yonghong Wu (Abstract and Applied Analysis)
By using the upper-lower solutions method and the fixed-point theorem on cone in a special space, we study the singular boundary value problem for systems of nonlinear second-order differential equations involving two parameters on the half-line. Some results for the existence, nonexistence and multiplicity of positive solutions for the problem are obtained.